Wind Turbine Aerodynamics II - Shen, Wen Zhong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is a collection of the latest research articles on various topics related to wind turbine aerodynamics, which includes wind turbine design concepts, tip loss correction study, wind turbine acoustics modelling, and the vertical axis wind turbine concept.